Cytokine soluble receptors in perinatal and early neonatal life - Protonotariou, E.; Rizos, D.; Malamitsi-Puchner, A.; Moira, E.; Sarandakou, A.; Salamalekis, E. (Mediators of Inflammation, 2003)
BACKGROUND: In contrast to cellular receptors, soluble receptors do not enhance the cellular activation because they do not have transmembranic and cytoplasmic parts, acting thereby as endogenous regulatory mechanisms against systemic functions of cytokines. Aim: To measure serum concentrations of the soluble interleukin-2 receptor (sIL2R), soluble interleukin-4 receptor (sIL4R), soluble interleukin-6 receptor (sIL6R), and soluble tumor necrosis factor-α receptor I and soluble tumor necrosis factor-α receptor II, during the perinatal and early neonatal period, in order to evaluate their role in activation of immune response in labor and the first days postpartum. Methods: Soluble receptor serum concentrations were determined by enzyme-linked immunosorbent assay, in 45 healthy, full-termed neonates during the first and fifth days after birth, in 25 of their mothers (MS), in 25 samples of umbilical cords (UC) and in 25 healthy adult donors age-matched with the mothers (controls). Results: Soluble receptor serum concentrations showed considerable changes during labor and early neonatal life, being significantly higher both in MS (except sIL6R) and in neonatal sample UC, first and fifth days after birth, compared with controls (p < 0.0001). Neonatal serum sIL2R and sIL6R increased significantly from birth to the fifth day, while the remaining receptors showed a rapid increase in the first day (p < 0.0001), declining significantly thereafter (p < 0.0001). Conclusion: Our Findings suggest that the elevated concentrations of all studied soluble cytokine receptors reflect the activation of immune response, and represent also regulatory protective mechanisms for mother and fetus-neonate against the systemic function of cytokines during labor and early neonatal life.
Keywords: Neonates; Soluble interleukin-2 receptor; Soluble interleukin-4 receptor; Soluble interleukin-6 receptor; Soluble tumor necrosis factor-α receptor I; Soluble tumor necrosis factor-α receptor II